2018
DOI: 10.21037/atm.2018.11.08
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Takotsubo cardiomyopathy: a comprehensive review

Abstract: Takotsubo cardiomyopathy (TTC) was first described in Japan in the 1980s. It is described as an acute but often reversible left ventricular (LV) dysfunction mainly triggered by emotional or physical stress.Multiple variants of TTC have been reported including reverse Takotsubo cardiomyopathy (rTTC) which is a variant characterized by the basal akinesis/hypokinesis associated with apical hyperkinesis that resolves spontaneously. The hallmark of rTTC is a clinical presentation similar to an acute coronary syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
84
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 41 publications
0
84
0
5
Order By: Relevance
“…11 This can be associated with dynamic electrocardiographic changes, ranging from transient ST elevations at onset subsequently transitioning to deep T-wave inversions followed by late normalization of T-waves. 3,5,[13][14][15][16][17] In contrast, patients with reverse TC usually present at a younger age and often have an emotional or physical trigger leading to basal and/or midventricular hypokinesis but preserved apical contractility, as seen in our patient. 18 Reverse TC is also typically more likely to be complicated by pulmonary edema and cardiogenic shock.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…11 This can be associated with dynamic electrocardiographic changes, ranging from transient ST elevations at onset subsequently transitioning to deep T-wave inversions followed by late normalization of T-waves. 3,5,[13][14][15][16][17] In contrast, patients with reverse TC usually present at a younger age and often have an emotional or physical trigger leading to basal and/or midventricular hypokinesis but preserved apical contractility, as seen in our patient. 18 Reverse TC is also typically more likely to be complicated by pulmonary edema and cardiogenic shock.…”
Section: Discussionmentioning
confidence: 59%
“…18 Reverse TC is also typically more likely to be complicated by pulmonary edema and cardiogenic shock. 5,19 The plausible underlying mechanisms for TC are sympathetic hyperactivity, multivessel transient coronary vasospasm, 8 estrogen deficiency, 9,17 and microcirculatory dysfunction. 5,9,20,21 There is a near-complete resolution of myocardial dysfunction in most patients usually within a few weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact mechanism leading to TTCM remains unknown. However, catecholamine-induced cardiotoxicity, microvascular dysfunction, stimulus trafficking, coronary vasospasm, and estrogen deficiency are the most prominent theories described behind its occurrence [10][11]. Several studies have shown that serum catecholamine levels are elevated during the acute phase of TTCM [2][3].…”
Section: Discussionmentioning
confidence: 99%